Circular business cannibalization: A hierarchical Bayes conjoint analysis on reuse, refurbishment, and subscription of home appliances - Koide, Ryu; Yamamoto, Haruhisa; Kimita, Koji; Nishino, Nariaki; Murakami, Shinsuke (Journal of cleaner production, 2023)
Despite the growing expectations of the transition to a circular economy, consumer preferences and the potential for circular products in a market in which multiple circular business models coexist are not well understood. Accordingly, here, in a case study of refrigerators in Japan, we applied a hierarchical Bayesian choice-based conjoint analysis to compare: i) purchasing brand-new, ii) purchasing reused, iii) purchasing refurbished, and iv) using a subscription to acquire products without a transfer of ownership. The estimated part-worth utilities show that older circular products are more accepted by consumers under the subscription or refurbished models than under the traditional reuse model. Four distinct consumer segments—subscription-prone (12%), price-sensitive (13%), balanced decision-makers (25%), and brand-new stubborn (51%)—were identified using ensemble clustering based on individual-level part-worth utilities. Market simulations under eight scenarios revealed significant cannibalization among multiple business models, such as reduced sales of reused products due to the introduction of a subscription system. Consequently, the potential market share of circular products was shown to be at most 35% when there are coexisting circular business models, which is less than the sum of the shares and assuming separate business models. The potential market share across consumer segments is quite diverse (e.g., as much as 50–90% for the ‘subscription-prone’ and ‘price-sensitive’ segments, whereas ‘brand-new stubborn’ consumers never choose circular products). However, if consumers screen out alternatives that are not in their awareness set (known alternatives) or consideration set (alternatives evaluated in the last phase of decision-making), the potential market share could be as low as 11%, implying that approaching the early phase of screening in the consumer decision-making process is crucial. The proposed approach can be used to improve the design of business models and policies for a circular economy that considers cannibalization among multiple circular models, consumer heterogeneity, and bounded rational decision-making.